Pengaruh Manajemen Strategi terhadap Peranan TIM Pengendalian Inflasi dalam Menstabilkan Harga Pangan di Kota Tanjungbalai (Studi Kasus Minyak Goreng Bersubsidi) - Aprilia Indah Saputri Rambe; Suhairi Suhairi (Universitas Muhammadiyah Enrekang, 2022)
The economy in an area is influenced by several factors. One of the factors is inflation. Inflation is an economic condition that shows a general and continuous tendency to increase the price level. Inflation is one of the benchmarks for people's purchasing power and macroeconomic stability.The use of this study is intended to analyze the effect of strategic management on the role of the regional inflation control team in stabilizing food prices in Tanjungbalai City. Then this research is divided into two parts, the first is to see how the government's strategy is, namely the role of TPID in overcoming inflation control in the scarcity of subsidized cooking oil in Tanjungbalai City and the second to find out the cause of the scarcity of subsidized cooking oil that occurs in Tanjungbalai City. The research method uses quantitative methods that use swot analysis.